Pelatihan Intensive and Children Care Parenting pada Masyarakat Kurang Mampu di Desa Kedamin Hulu - Wijio, Sarono; Zuhdi, Muh. Sholihudin (Altruism: The Indonesian Journal of Community Engagement, 2025)
Knowledge about parenting is still a homework assignment in Indonesia, including in the villages of Kedamin Hulu, Putussibau, Kapuas Hulu. The initial survey stated that there were still some parents who did not understand good, correct, and appropriate parenting according to the conditions of their children and families. This service aims to provide knowledge and parenting skills that are appropriate to the conditions of each family. Your choice of intensive parenting care is most appropriate to the conditions in the field. This service uses participatory rural appraisal using a quasi-experimental approach. Participants take part in a series of pretests, treatment, and posttests. There were 25 service participants consisting of men and women. The results of the service show that there are significant changes in the knowledge and parenting behavior of service participants. This shows that service activities with an intensive and caring parenting approach can be well received. This activity can be expanded in scope so that it has a wider impact.